2010
DOI: 10.1111/j.1600-0889.2010.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of urban air pollution from MODIS aerosol data: effect of meteorological parameters

Abstract: A B S T R A C T Remote sensors designed specifically for studying the atmosphere have been widely used to derive timely information on air pollution at various scales. Whether the satellite-generated aerosol optical thickness (AOT) data can be used to monitor air pollution, however, is subject to the effect of a number of meteorological parameters. This study analyses the influence of four meteorological parameters (air pressure, air temperature, relative humidity, and wind velocity) on estimating particulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
2
13
2
Order By: Relevance
“…Higher correlation coefficients and slopes were observed at urban sites (R = 0.466; Slope = 68.12) than suburban sites (R = 0.324, Slope = 37.98). Also, higher correlation coefficients were observed in summer (R = 0.453) and fall (R = 0.428) than those in spring (R = 0.392) and winter (R = 0.200).Such variations have also been reported in other studies (Tian and Chen, 2010;Zha et al, 2010).For example, Tian and Chen (2010) suggested that the correlation between AOT and PM was stronger in the spring and summer while weaker in the fall and winter for the area of southern Ontario. Zha et al (2010) found a minimum correlation coefficient between AOT and PM for the season of winter (R = 0.47), but a much stronger correlation (R > 0.80) in summer and autumn for the city of Nanjing in China.…”
Section: Aot-pm 10 Regression Modelssupporting
confidence: 81%
See 1 more Smart Citation
“…Higher correlation coefficients and slopes were observed at urban sites (R = 0.466; Slope = 68.12) than suburban sites (R = 0.324, Slope = 37.98). Also, higher correlation coefficients were observed in summer (R = 0.453) and fall (R = 0.428) than those in spring (R = 0.392) and winter (R = 0.200).Such variations have also been reported in other studies (Tian and Chen, 2010;Zha et al, 2010).For example, Tian and Chen (2010) suggested that the correlation between AOT and PM was stronger in the spring and summer while weaker in the fall and winter for the area of southern Ontario. Zha et al (2010) found a minimum correlation coefficient between AOT and PM for the season of winter (R = 0.47), but a much stronger correlation (R > 0.80) in summer and autumn for the city of Nanjing in China.…”
Section: Aot-pm 10 Regression Modelssupporting
confidence: 81%
“…Despite similar results observed in these studies, different explanations were given for these seasonal variations. In Tian and Chen's study (2010), the wavelength, at which the AOT product was derived from MODIS, was expected to be closely associated with the correlation between AOT and PM; while Zha et al (2010) reported that high pollution levels may reduce the accuracy of MODIS monitoring data in winter. Previous study also reported that MODIS retrieving algorithms has relatively good capability of retrieving fine mode aerosols (with effective radius between 0.1 µm to 0.25 µm), while poor ability for retrieving coarse mode aerosol (with effective radius between 1.0 µm to 2.5 µm) due to currently lack of MODIS data over high reflectance of natural dust sources (Dubovik et al, 2007;Santese et al, 2007).…”
Section: Aot-pm 10 Regression Modelsmentioning
confidence: 99%
“…Additionally, MODIS AOD was also not available on certain days because of cloud cover. The observed correlation of r = 0.67 is quite good and is in agreement with the range stated in previous studies [89][90][91][92] for similar kinds of comparison. Furthermore, the correlation depends on various factors such as seasonal variation, meteorological parameters, spatial resolution of the satellite pixel (10 km in this case) and aloft aerosol layer [89][90][91][92].…”
Section: Case Study-winter 2014-2015supporting
confidence: 80%
“…Therefore, PM 10 both summer and autumn have an improved accuracy while the accuracy for the spring and winter seasons is lower. In other words, the air pollution conditions recorded in satellite imagery are able to depict the pollution level better during June-November than during the rest of the year [16]. The likely reason to account for the varying degree of prediction accuracy is the meteorological conditions in different seasons that control the circulation of pollutants in the atmosphere.…”
Section: Relationship Between Pm 10 and Aot And Its Seasonal Variabilitymentioning
confidence: 99%